Multifaceted Roles of Nurses in Mitigating Climate Change-Related Health Impacts: A Scoping Review - Nadia Rohmatul Laili; Apriana Rahmawati; Arina Qona'ah (Journal of Public Health Sciences, 2026)
Climate change is increasingly amplifying global morbidity and mortality, disproportionately affecting vulnerable populations and placing sustained pressure on health systems. Nurses, as the largest segment of the healthcare workforce, are strategically positioned to mitigate climate change-related health impacts; however, the scope and empirical basis of these roles remain insufficiently consolidated. This scoping review aimed to map and critically examine the multifaceted roles of nurses in addressing climate-related health consequences. A comprehensive search of SCOPUS, PubMed, ProQuest, and ScienceDirect identified 15 articles eligible for inclusion in this review. Four core nursing roles were identified: (1) integrating climate change into nursing curricula and community health education, (2) advancing research on planetary health, (3) influencing climate-related health policies, disaster preparedness, and resilience strategies, and (4) providing climate-responsive care to vulnerable populations. A key finding was the predominance of normative and conceptual literature, revealing a substantial gap between expected nursing roles and empirically supported practices, particularly in direct caregiving interventions.